Additively manufactured injection mould tooling incorporating gradient density lattice structures for mass and energy reduction - Rokas Šakalys; Christopher O'Hara; Mandana Kariminejad; Albert Weinert; Mohammadreza Kadivar; Bruno Zluhan; Karl Costello; Marion McAfee; Gerard McGranaghan; Ramesh Raghavendra; David Tormey (International Journal of Lightweight Materials and Manufacture, 2025)
The benefits of reducing the mass of injection moulding (IM) tooling include opportunities to also reduce material and energy consumption of the Additive Manufacturing L-PBF (Laser Powder Bed Fusion) processes, leading to lower overall costs for the IM setup. This provides a competitive advantage and reduces the environmental impact of the tool-making process in comparison to manufacturing heavier IM tooling. Mass reduction of tooling by using complex internal geometries like lattice structures, which are impossible to achieve using subtractive fabrication approaches, can be easily implemented through additive manufacturing (AM). Therefore, this research exploits the combination of lattice structure design and AM to make functional IM tooling. A tooling design with solid infill was initially modified with a lattice structure of uniform strut thickness, and then Finite Element (FE) Structural Analysis was performed to estimate the stress field typical of an injection mould cycle. Based on these results, a field-driven approach was further applied to alter the lattice structure into a variable gradient strut thickness lattice, aiming for an additional mass reduction. The tooling was additively manufactured using L-PBF technology and successfully applied in the IM process. Mass reductions of 21.86 and 23.95 % were achieved for moving and fixed halves respectively; this corresponds to laser energy savings of 11.06 and 13.44 %. The tooling demonstrated complete functionality during the industrial IM process producing parts within the design specification.